A Multi-Criteria Decision-Making Approach to Workforce Optimization in Public Sector Organizations - Ghaziani, Khadijeh; Esfandiari, Mahmoud (Annals of Optimization With Applications, 2026)
This study aims to propose strategies for optimizing the workforce in governmental organizations through a Multi-Criteria Decision-Making (MCDM) approach, applied to the Foundation of Martyrs and Veterans Affairs of Mazandaran Province. The research employs a mixed-methods methodology, including a systematic literature review, a three-round Delphi process with 15 experts, the BWM, and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The Delphi results identified 41 components across five dimensions: Structural, skill-based, technological, behavioral, and economic. The BWM ranked the skill-based dimension as the most significant, with a weight of 36.2%. The TOPSIS method identified three top-priority strategies: continuous training, talent management, and succession planning. Sensitivity analysis confirmed the robustness of the model. The novelty of this research lies in the development of a hybrid model integrating the Delphi method, the Best–Worst Method, and TOPSIS, applied for the first time within the Foundation of Martyrs. This model enhances decision-making processes by transitioning from experience-based to scientifically grounded approaches. Furthermore, it addresses a knowledge gap in integrated workforce planning in the public sector and, by prioritizing competency-based approaches, increases productivity by 25% to 35%. It is recommended that the organization consider establishing a competency development center, implementing job rotation, and deploying an intelligent dashboard system. The proposed model is suggested as a generalizable framework for veterans’ institutions and other governmental organizations.